Évolution d’un îlot urbain du xiiie au xviie siècle, Quimper, Collège de la Tour d’Auvergne (Finistère) - Françoise Le Boulanger (Archéologie Médiévale, 2004)
In 1998, a rescue excavation provided the opportunity of studying an entire urban building plot occupied from the 13th to the early 17th century A.D. The spatial and chronological evolution of this 960 m2 area has been retraced. It is characterised by three main occupation phases. The earliest occupation is Medieval (13th century at least) and is materialised by poorly preserved negative features. The erection of masonry buildings corresponds to the second and most consequential phase (14th – early 17th century). In its last state, four buildings with latrines are disposed around a paved courtyard itself organised around a well, with a terraced garden nearby. Modifications to the waste water disposal system have been recorded. The final phase consists in the destruction of these quarters in order to create a terraced garden for the recently established Jesuit college (mid 17th century). For each of these major episodes, we dispose of a pottery assemblage, and sometimes glass. This study fits in well with current research themes on the house in its urban context, particularly in this region for which data is scant. It also helps to establish a general view of Medieval Quimper.